Employability skills development approaches: an application of the analytic network process - Abdul Hamid, Mohamad Shukri; Islam, Rafikul; Abd. Manaf, Noor Hazilah (Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2014)
Institutions of higher learning need to re-evaluate their teaching-learning approaches to develop the necessary employability skills for their graduates. The main objectives of this study are to identify the important employability skills and the corresponding employability skills development approaches in a Malaysian setting. The results of the application of an analytic network process (ANP) show that the 'ability to speak fluently in English' is the most important skill, followed by the 'ability to write effectively in English' and the 'ability to think critically'. On the other hand, the most effective employability skills development approach is found to be 'work-integrated learning'. The other effective approaches are identified as 'stand-alone subject model', 'academic support programme', 'embedded subject model', 'non-academic support programme' and 'campus life activities'.